A WOMANâS IDENTITY AS DEPICTED IN ANGELOUâS POEM âWOMAN WORKâ - , AYU SHADRINA SARASWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This graduating paper analyzes Maya Angelouâs poem âWoman Workâ. This poem talks about identity which is described by Maya Angelou. The objective of this research is to study Maya Angelouâs search of identity through her feeling, thought, desire, and perspective which are depicted and discussed in the poem. This graduating paper uses an expressive approach because this approach is the most suitable for learning the poetâs perspective on woman identity through her works. Library research is employed to support the analysis. The result of the analysis implies that the speakerâs position is a woman who has a role in society as a mother, worker and slave depicted in the poem. The speaker carries out all jobs in house both inside and outside. However, the speaker expresses a process of her journey to find her identity which is reflected in the poem. The speaker tries to prove that identity is an important part of her qualities that are personality/characteristic that must be maintained. In this poem the speaker indicates that she becomes a woman who is more confident and proud. It is the result of her process of maturity that is expressed by her makes her realizes the truth of her identity. The speaker reveals the process of her life that is faced by her to display that she is a strong woman.